Quantifying similarity of pore-geometry in nanoporous materials - Yongjin Lee (Nature Portfolio, 2017)
Pore structure plays an important role in dictating gas storage performance for nanoporous materials. Here, Smit and colleagues develop a topological approach to quantify pore structure similarity, and exploit the resulting descriptor to screen for materials that possess structural similarities with top-performers.